Islamic Society Diaspora of Bugis Descent in Bali - Suwitha, I Putu Gede (International Research Journal of Management, IT & Social Sciences, 2016)
Diaspora Islamic Society of Bugis descent in Bali has long played a role, especially in the political and economic fields. Their presence has historically never to be an issue, due to political entity that became a patron. Besides that, the cultural exchanges in various activities has been made inter-ethnic relations and more collaborative than competitive. This study was wanted to express how diaspora was formed in Bali island of Hindu society. Similarly, the development of Islam Bugis and how relationship between diaspora Bugis. The results of this study that showed in addition to Bugis diaspora demonstrate their role, as well as in their diasporic make an adjustments and establish a new identity. The identity was a diaspora community needs. Public spaces has been built and part of a multicultural society and mem blow values up the Baliness people, recently, the Bugis community in a state of marginalized (subaltern). Spivak (1972) stated that seems subaltern merkea not be able to follow the dynamics of changing, especially, in the world of tourism in Bali.